Increasing Broiler Business with a Strategy Without AGP in People's Farms Based on Production Aspects and Economic Aspects - Rijanto Japutra, Bambang; Ismoyowati, Ismoyowati; Andri Setianto, Novie; Rayhan, Muhammad; Harnowo Sidhi, Arif; Hindratiningrum, Novita (Bulletin of Applied Animal Research, 2024)
This study examines the improvement of broiler chickens using AGP and without AGP aims to determine the difference between the use and removal of antibiotic growth promoter (AGP) in broiler chicken feed based on production aspects (feed efficiency and cumulative performance index), economic aspects (business capacity and income), socio-demographic aspects (breeder education, age of breeder, duration of breeding and motivation to raise livestock), analyzing various factors and their relationship in broiler farming in Banyumas district, Pemalang district, Temanggung district, and Banjarnegara district, Central Java province. This research was conducted using a survey method on broiler breeders who joined a partnership company. Data analysis consisted of analysis of variance based on GLM (general linear model). The results of the phase 1 study showed that there were differences in production aspects (EFF and IPK) in different years, districts, and business scales, but the use and elimination of AGP on feed efficiency and cumulative performance index showed no significant differences. Broiler production was better in 2018 with the elimination of AGP than in 2017 when using AGP in the manufacturer's feed. Based on the economic aspect, the use and elimination of AGP have no significant effect on business capacity and income. Scientifically, it is necessary to carry out further research and development of quantitative models. The implications of efforts to improve the broiler farming business system on smallholder farms include: 1) breeders have land and cages with minimal quality, namely semi-closed houses, 2) partnership companies partner with farmers who have livestock education background, 3) improve maintenance management based on quality. SAPRONAK used. Therefore, in the development of the broiler farming business, it is necessary for the Government to also pay attention to the regulatory system and arrangement of the broiler marketing trade system as an effort to increase the productivity of the broiler farming business.